2009
DOI: 10.1021/ic802087n
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium Phthalocyanine-Bipyridyl Dyads as Sensitizers for Dye-Sensitized Solar Cells: Dye Coverage versus Molecular Efficiency

Abstract: The application of ruthenium phthalocyanine complexes as sensitizing dyes in dye-sensitized solar cells (DSCs) is explored. Four monomeric complexes are reported which vary in peripheral substitution and axial ligand anchoring groups. Sensitizing dyes containing two ruthenium centers are also presented. These dyads, which contain ruthenium phthalocyanine and bipyridyl chromophores, were prepared using a protection/deprotection strategy that allows for convenient purification. DSCs fabricated using the phthaloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 65 publications
4
41
1
1
Order By: Relevance
“…Complex 1 also has a broad low intensity absorption band centred at 426 nm. Similar absorption bands have previously been observed in the electronic spectra of [PcRuL 2 ] complexes where L = (2-oxopropyl)pyridine-4-carboxylate [13] or pyrazine [21] and are attributed to metalto-ligand charge-transfer (MLCT). The spectrum of the dimeric complex 2 is also dominated by the Q-and Soret bands and the molar absorptivities of these bands are greatly increased relative to the monomeric complexes due to the two phthalocyanine rings per molecule.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…Complex 1 also has a broad low intensity absorption band centred at 426 nm. Similar absorption bands have previously been observed in the electronic spectra of [PcRuL 2 ] complexes where L = (2-oxopropyl)pyridine-4-carboxylate [13] or pyrazine [21] and are attributed to metalto-ligand charge-transfer (MLCT). The spectrum of the dimeric complex 2 is also dominated by the Q-and Soret bands and the molar absorptivities of these bands are greatly increased relative to the monomeric complexes due to the two phthalocyanine rings per molecule.…”
Section: Introductionsupporting
confidence: 74%
“…In addition, thin films of PcRu complexes on surfaces have been generating increased interest [1,11] with applications in areas such as photovoltaics [12][13][14][15] and sensors [16]. We have recently reported that ruthenium phthalocyanine complexes bearing axial ligands with thioacetate groups can form thin films on gold surfaces [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 and Table 2) porphyrin sensitizers were reported in 2009. [103][104][105][106][107] Although phthalocyanines have some advantages for DSSC applications with respect to porphyrins such as strong absorption in the red (Q band at B700 nm), p-type semiconducting properties and thermal stability, 107 they suffer some limitations such as very poor solubility and strong aggregation when deposited on the surface of the semiconductor. 108 With a structural design involving long alkoxyl chains to enclose the porphyrin core (YD2-o-C8 dye) suppressing the dye aggregation suffered by zinc porphyrins, 303 the DSSC achieved Z = 12.3% in 2011 with co-sensitization of a synthetic organic dye (Y123, a donor-p-bridge acceptor) and a cobalt-based electrolyte.…”
Section: Synthetic Organic Dyesmentioning
confidence: 99%
“…[1][2][3] Up to now, DSSCs based on metal-free organic dyes, 4-7 porphyrin dyes, [8][9][10] metalphthalocyanine, 11,12 and natural dyes 13,14 have been reported and developed. Although the efficiencies of DSSCs have not yet approached the theoretical limit and are not competitive with the silicon-based solar cells, organic dyes have their own advantages, 15 such as low cost, high absorption coefficient and easy control of redox potentials of the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) levels.…”
Section: Introductionmentioning
confidence: 99%